High-Grade Fetal Vascular Malperfusion Is Associated With Diffuse Chorionic Hemosiderosis. (May 2022) - Mooney, Eoghan E.; Crotty, Emma
Introduction: Diffuse chorionic hemosiderosis (DCH) is an abnormality of the placental membranes characterized by the deposition of iron pigment. It is usually secondary to recurrent venous bleeding in early pregnancy. In many papers, it is associated with pre-term delivery. Fetal vascular malperfusion (FVM) is an abnormality of the feto-placental circulation that may be seen at any stage of gestation, but most often in the third trimester. It may be graded as low grade (LGFVM) or high grade (HGFVM). No link has been identified in the placental literature between DCH and FVM, but we have noted the 2 co-existing in placentas submitted for analysis. This study explored a possible association of these 2 entities. Methods: Laboratory records were searched for singleton cases coded as DCH based on diagnosis on H&E stain over a 6-year period. Of 4478 placentas reported, 66 cases were coded as DCH (1.5%). These were classified as showing HGFVM, LGFVM, or no FVM. Controls (n = 132) were gestational age-matched cases without DCH. Cord length, coiling, insertion, or other abnormalities were noted. Membranes were classified as normal or circumvallate. Results were analyzed using Graphpad. Results: Gestation ranged between 16 and 41 weeks gestation. 14/66 (21%) cases of DCH showed HGFVM and 2/66 (3%) showed LGFVM. 16/132 (12%) controls showed HGFVM and 21/132 (15.9%) had LGFVM. Where FVM is present, high-grade FVM is significantly associated with DCH versus controls ( P < .0031 Fischer's Test). Discussion: HGFVM occurs significantly more often in placentas with DCH than in controls. Both FVM and DCH are associated with adverse perinatal outcomes, and a possible relationship between the 2 remains to be clarified.